2005
DOI: 10.1073/pnas.0501744102
|View full text |Cite
|
Sign up to set email alerts
|

Collecting duct-specific deletion of peroxisome proliferator-activated receptor γ blocks thiazolidinedione-induced fluid retention

Abstract: The peroxisome proliferator-activated receptor subtype ␥ (PPAR␥) ligands, namely the synthetic insulin-sensitizing thiazolidinedione (TZD) compounds, have demonstrated great potential in the treatment of type II diabetes. However, their clinical applicability is limited by a common and serious side effect of edema. To address the mechanism of TZD-induced edema, we generated mice with collecting duct (CD)-specific disruption of the PPAR␥ gene. We found that mice with CD knockout of this receptor were resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
269
2
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(287 citation statements)
references
References 49 publications
4
269
2
9
Order By: Relevance
“…Shortterm animal studies also show that there is a rapid increase in body weight during the first week of treatment, clearly due to an increase in water content [6,7] and an increase in the epithelial sodium channel (ENaC) activity. These effects were inhibited by amiloride, an ENaC inhibitor, and abolished in mice with specific deletion of the collecting duct PPAR-γ suggesting an important role of glitazoneinduced sodium retention through ENaC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shortterm animal studies also show that there is a rapid increase in body weight during the first week of treatment, clearly due to an increase in water content [6,7] and an increase in the epithelial sodium channel (ENaC) activity. These effects were inhibited by amiloride, an ENaC inhibitor, and abolished in mice with specific deletion of the collecting duct PPAR-γ suggesting an important role of glitazoneinduced sodium retention through ENaC.…”
Section: Discussionmentioning
confidence: 99%
“…Both direct and indirect effects of glitazones on renal sodium reabsorption have been proposed, through the direct activation of tubular peroxisome proliferator-activated receptor (PPAR)-γ or indirectly through the activation of compensatory mechanisms secondary to the glitazone-induced vasodilation [6][7][8]. Experimental studies have shown that glitazones may increase sodium transport in the proximal convoluted tubules, the thick ascending limb and the collecting duct [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A high-energy state, such as obesity, is associated with disturbance of electrolytes and fluid balance and hypertension (46,47), whereas a low-energy state, such as fasting, induces natriuresis and diuresis (48,49). Along this line, activation of PPARγ, a key regulator of glucose metabolism and adipogenesis, causes body weight gain and plasma volume expansion (50,51). In the present study, we discovered that LXR against TO901317 exerted a profound diuretic action in mice as suggested by polyuria, polydipsia, hypoosmotic urine, and contraction of plasma volume.…”
Section: Induction Of Diabetes Insipidus and Suppression Of Renal Prrmentioning
confidence: 99%
“…Therefore, the volume retaining effect of PPARγ-agonists may be due to stimulation of the epithelial sodium channel (ENaC) in the distal nephron [26]. Accordingly, gene-targeted mice with a collecting duct-specific deletion of PPARγ are apparently protected against PPARγ agonists-induced fluid retention [51].…”
Section: Introductionmentioning
confidence: 99%